Learning Mobile App Design from User Review Analysis - Platzer, Elisabeth; Petrovic, Otto (International Journal of Interactive Mobile Technologies (iJIM), 2011)
This paper presents a new learning environment for developers of mobile apps that merges two quite different views of the same topic. Creative design and system engineering are core issues in the development process that are based on diverging principles. This new learning environment aims to address both points of view by not suppressing one of them but trying to benefit from both. User review content analysis is introduced as a tool to generate information that is useful for both aspects.